2016
DOI: 10.1210/jc.2016-1300
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and the Risk of Nonalcoholic Fatty Liver Disease: The Rotterdam Study

Abstract: Lower thyroid function is associated with an increased NAFLD risk. These findings may lead to new avenues regarding NAFLD prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
159
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 41 publications
10
159
1
6
Order By: Relevance
“…Recently, a publication from the Rotterdam group has also found a positive association between the prevalence of NAFLD and TSH levels [26]. The group was able to demonstrate that the risk of NAFLD progressively decreased from a hypothyroid to a hyperthyroid state [26]. However, in both studies, there was no analysis within the normal reference range.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, a publication from the Rotterdam group has also found a positive association between the prevalence of NAFLD and TSH levels [26]. The group was able to demonstrate that the risk of NAFLD progressively decreased from a hypothyroid to a hyperthyroid state [26]. However, in both studies, there was no analysis within the normal reference range.…”
Section: Discussionmentioning
confidence: 98%
“…In 2012, a Korean study showed that NAFLD was statistically significantly associated with hypothyroidism and subclinical hypothyroidism in a dose-dependent manner, independently of metabolic syndrome risk factors [27]. Recently, a publication from the Rotterdam group has also found a positive association between the prevalence of NAFLD and TSH levels [26]. The group was able to demonstrate that the risk of NAFLD progressively decreased from a hypothyroid to a hyperthyroid state [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicated that there was a need for better understanding of the crosstalk effects between NAFLD, hyperuricemia, and HTN in diabetes. Two very recent studies reported [39, 40] that the higher free thyroxine levels were associated with a decreased risk of NAFLD. In our study, the higher T3 levels were related to an increased risk of HTN in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%